The inclusion of Philosophy of Science (PoS) in science curriculum at Malaysian public universities - Saidon, Mohd Fazli; Mohd Shafri, Mohd Affendi; Zamli, Zaitunnatakhin (2014)
INTRODUCTION: Philosophy of science was often included in medical curriculum in ancient times and continued to be taught in established medical faculties throughout the world. New medical science faculties in post-modern era, however, tend to neglect the inclusion of philosophy in their new curriculum. The trend is changing with increasing number of departments of philosophy at medical science-based faculties, philosophy-related societies, conferences and journals worldwide. The study looks at how the global trend is affecting Malaysian public universities by identifying universities offering the subject, finding out challenges in its delivery, and how it is currently perceived at the universities. MATERIALS AND METHODS: Online survey was conducted over a 3 months period in 2013 and sent via email to 300 randomly selected academicians from every Malaysian public university. Participation was voluntary and was divided into two groups: (a) universities that include (n=14) and (b) universities that exclude (n=14) the teaching of PoS. RESULTS AND DISCUSSION: In the first group, 63, 70 and 78% of respondents answered favourably that teaching of PoS will solve student’s ethics problem, is useful for student’s future career and will lead to the development of critical thinking. In the second group, the same questions get 57, 57 and 71% favourable answers. Among those, 57% would like PoS to be included in the curriculum. Lack of suitable lecturer and unavailability of PoS curricula are the most common reasons for exclusion. There is generally no plan to introduce PoS in the universities that does not offer the subject presently. In terms of teaching methodology, the most commonly used method is lecture, and differences in teaching methodology are not thought to influence students’ performance. CONCLUSION: In conclusion, teaching of PoS in science curriculum in Malaysian public universities does not appear to follow current global trend while awareness is low on what constitute PoS and why it is important.